Тайна старого кладбища: повесть / А. Д. Иванов, А. В. Устинова - Иванов А. Д. (Детективное агентство, 2007)
Экземпляры: (20220310) / Инвентарный номер: 3602 / Цена: / Сис.шифр: 84(2Рос)6 / Авт.знак: И 20 / ББК: 84(2Рос)6